Role of circular RNAs in lung cancer - Babayev, Maksat; Silveyra, Patricia (Frontiers in Genetics, 2024)
Lung cancer remains a global public health concern with significant research focus on developing better diagnosis/prognosis biomarkers and therapeutical targets. Circular RNAs (circRNAs) are a type of single-stranded RNA molecules that are covalently closed and have ubiquitous expression. These molecules have been implicated in a variety of disease mechanisms, including lung cancer, as they exhibit oncogenic or tumor suppressor characteristics. Recent research has shown an important role that circRNAs play at different stages of lung cancer, particularly in lung adenocarcinoma. In this review, we summarize the latest research on circRNAs and their roles within lung cancer diagnosis, as well as on disease mechanisms. We also discuss the knowledge gaps on these topics and possible future research directions.